Adverse Collateral Effects of COVID-19 Public Health Restrictions on Physical Fitness and Cognitive Performance in Primary School Children - Camille Chambonnière (MDPI AG, 2021)
The aim of the present study was to evaluate whether the COVID-19-related confinement and social restrictions affected the levels of physical fitness and academic achievement in primary school French children. A total of 206 primary school children (106 before confinements and 100 after restrictions) completed a test battery evaluating their anthropometric characteristics, body compositions, activity preferences, cognitive performances and physical fitness. The performance of the Standing Long Jump was better at T0 (169.9 ± 142.5 cm) compared to T1 (135.2 ± 31.4 cm) (p = 0.0367), and the Medicine Ball Throw performance declined from T0 to T1 (297.3 ± 81.1 cm vs. 249 ± 52 cm; p < 0.0001). Motor skills (26.9 ± 6.2 s vs. 30.9 ± 5.4 s; p < 0.0001), the shuttle-run test (stages completed), Maximal Aerobic Speed, and the estimated VO2max were lower at T1 compared to T0 (p < 0.0001). Executive functioning was found to be greater at T0 compared to T1 (p < 0.0001). Explicit liking or wanting for sedentary or physical activities did not change between T0 and T1. Both overall physical fitness and cognitive performance drastically declined among primary school French children with the COVID-19-related public health restrictions, which reinforces the need to urgently develop preventive strategies in anticipation of further mitigation measures.